Can exit prizes induce lame ducks to shirk less? Experimental evidence - Leif Helland; Jon Hovi; Lars Monkerud (European Journal of Government and Economics (EJGE), 2012)
Elected representatives serving their final period face only weak incentives to provide costly effort. However, overlapping generations (OLG) models suggest that exit prizes sustained by trigger strategies can induce representatives in their final period to provide such effort. We evaluate this hypothesis using a simple OLG public good experiment, the central treatment being whether exit prizes are permitted. We find that a significantly higher number of subjects in their final period contribute when exit prizes are permitted. However, this result does not originate from use of trigger strategies. More likely explanations include gift-exchange and focal-point effects.
Keywords: 330; overlapping generations; last period effects; legislatures